The archaeology of Kenilworth Castle's Elizabethan garden : excavation and investigation 2004-2008 - Dix, Brian F., (Archaeopress archaeology., 2017)
As part of the Property Development Programme for Kenilworth Castle, Warwickshire, English Heritage created an ambitious reconstruction of the former Elizabethan garden on the north side of the castle keep. In order to achieve a reliable representation of the original garden, a team with a broad range of specialist knowledge was brought together to advise first upon the practicality of undertaking the project and then to assist in the delivery of its design. Related detailed studies have been assembled in an English Heritage monograph edited by Anna Keay and John Watkins (2013).